OBJN and online video-publication - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The Online Brazilian Journal of Nursing (OBJN) will be soon an online video-publication for nursing and health research